Urinary Lysosomal Enzyme Activities and Albuminuria in Ghanaian Patients with Type 2 Diabetes Mellitus - Asare-Anane, H.; Twum, F.; Kwaku Ofori, E.; Torgbor, E.L.; Amanquah, S.D.; Osafo, C. (Disease Markers, 2016)
Renal tubular lysosomal enzyme activities like alanine aminopeptidase (AAP) and N-acetyl- β -D-glucosaminidase (NAG) have been shown to increase in patients developing diabetic nephropathy and nephrosclerosis. This study aimed to determine the activities of N-acetyl- β -D-glucosaminidase and alanine aminopeptidase and albumin concentration in urine samples of patients with type 2 diabetes. One hundred and thirty (65 type 2 diabetic and 65 nondiabetic) subjects participated in this study. Blood samples were drawn for measurements of fasting blood glucose, albumin (Alb), lipids, and creatinine (Cr). Early morning spot urine samples were also collected for activities of alanine aminopeptidase (AAP), N-acetyl- β -D-glucosaminidase (NAG), and concentration of albumin (U-Alb) and creatinine (U-Cr). Both NAG/Cr and AAP/Cr were significantly increased in diabetic subjects compared to controls (p < 0.001). There was positive correlation between NAG/Cr and Alb/Cr (r = 0.49, p < 0.001) and between NAG/Cr and serum creatinine (r = 0.441, p < 0.001). A negative correlation was found between NAG/Cr and eGFR (r = - 0.432, p < 0.05). 9.3% and 12% of diabetics with normoalbuminuria had elevated levels of AAP/Cr and NAG/Cr, respectively. We conclude that measuring the urinary enzymes activities (NAG/Cr and AAP/Cr) could be useful as a biomarker of early renal involvement in diabetic complications. © 2016 Henry Asare-Anane et al.